2010
DOI: 10.1029/2009gb003737
|View full text |Cite
|
Sign up to set email alerts
|

Influence of atmospheric nutrients on primary productivity in a coastal upwelling region

Abstract: [1] Atmospheric deposition is an important source of nutrients to the coastal and open ocean; however, its role in highly productive upwelling regions like coastal California has not been determined. Approximately 0.1%-0.2% of new production is attributable to atmospheric deposition of nitrogen (N) annually, but if the estimate is expanded to encompass the effects of iron (Fe), aerosols may support 1%-2% of new production on average, and up to 5% on days with high deposition fluxes. Laboratory culture and in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 104 publications
4
42
0
Order By: Relevance
“…Global-scale increases in rainfall may be attributed to a 4% rise of water vapor content of the atmosphere since 1970 (Milly et al, 2002;Trenberth et al, 2005;Santer et al, 2007;Pall et al, 2011), but more locally, effects have been spatially patchy, with increased rain in Panama and Colombia, while Brazil suffered droughts (Malhi et al, 2008;Marengo et al, 2008;Lewis et al, 2011;Min et al, 2011). It has been suggested that such shifts in rainfall within this part of the world may be associated with climate-driven changes in El Niño Southern Oscillation (ENSO), and, particularly, the increases in rain may be linked to rainy seasons influenced by La Niña phases of the cycle (Mackey et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…Global-scale increases in rainfall may be attributed to a 4% rise of water vapor content of the atmosphere since 1970 (Milly et al, 2002;Trenberth et al, 2005;Santer et al, 2007;Pall et al, 2011), but more locally, effects have been spatially patchy, with increased rain in Panama and Colombia, while Brazil suffered droughts (Malhi et al, 2008;Marengo et al, 2008;Lewis et al, 2011;Min et al, 2011). It has been suggested that such shifts in rainfall within this part of the world may be associated with climate-driven changes in El Niño Southern Oscillation (ENSO), and, particularly, the increases in rain may be linked to rainy seasons influenced by La Niña phases of the cycle (Mackey et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, nutrient input directly to the euphotic layer due to atmospheric deposition may become a relatively more important nutrient supply mechanism to the euphotic layer (Mackey et al, 2010;Okin et al, 2011;Mellard et al, 2011). However, few model studies (e.g., Mellard et al, 2011) have explored the influence of external surface nutrient supply on vertical phytoplankton distribution.…”
Section: In the Presence Of Surface Nutrient Inputmentioning
confidence: 99%
“…Although deposition of natural aerosols supports marine productivity globally by supplying macronutrients (nitrogen (N), Duce et al, 2008, phosphorus (P), Herut et al, 1999;Mackey et al, 2012b) and trace metals (Mahowald et al, 2005;Mackey et al, 2010;Mackey K. R. et al, 2012), anthropogenic aerosols tend to have much higher proportions of N relative to P (Duce et al, 2008;Kim et al, 2011), and provide more soluble trace metals than natural particles (Uematsu et al, 2010;Sholkovitz et al, 2012;Mackey et al, 2015b). As such they can alter phytoplankton population dynamics and favor species that would not bloom under natural conditions.…”
Section: Introductionmentioning
confidence: 99%